Pendidikan Islam Dalam Konteks Dakwah dan Thalabul ‘Ilmi - Mohammad Muslih (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
This article discusses about Islamic education in relation to dakwahand thalabul ilmi. Although it is actually a common issue that has been sostrong in views of society, then the discussion is to intended to reaffirm. Butmore than that, try to do a new meaning to the concept of dakwah andthalabul ‘ilmi, in relation to Islamic education. on the one hand, this is doneto avoid the wrong understanding and counterproductive activity. on theother hand, to maximize the Islamic education’s role in the development ofthe people and the development of civilization. In the context of dakwah,education means success in the underlying human life to enter a period ofproductivity and Creativity. While in the context of thalabul ‘ilmi, educationis more than just teach science, but create the true learner, developer ofscience, even the inventor of the theory and methodology in a variety ofscience. So, thalabul ‘ilmi has significance in answering the challenges ofscience, even preparing to build civilization.